2011
DOI: 10.4038/sljch.v40i2.3090
|View full text |Cite
|
Sign up to set email alerts
|

A clinical audit of thalassaemia management at the Lady Ridgeway Hospital for Children, Colombo

Abstract: Objective: To assess the adherence of management of beta thalassaemia major patients at Lady Ridgeway Hospital to an established standard treatment protocol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Hence, nutritional care is very important in the management of thalassemia. The mean number of blood transfusions in a Sri Lankan study was 10.4 in the past year which was similar to our observations [18]. In the study done at Ahmedabad, India, the frequency of transfusion was once or more in a month among 25.6% cases which were also similar to our findings [19].…”
Section: Original Research Articlesupporting
confidence: 90%
“…Hence, nutritional care is very important in the management of thalassemia. The mean number of blood transfusions in a Sri Lankan study was 10.4 in the past year which was similar to our observations [18]. In the study done at Ahmedabad, India, the frequency of transfusion was once or more in a month among 25.6% cases which were also similar to our findings [19].…”
Section: Original Research Articlesupporting
confidence: 90%
“…It revealed that these factors do not have any impact on the HRQoL of children with thalassemia similar to previous studies [11,17]. Further, all these patients were basically managed by the government sector hospitals where the blood transfusion facilities are available [8]. Therefore, this is a mark of the improvement of quality of care given to the thalassemia patients in Sri Lanka during the last few decades.…”
Section: Discussionsupporting
confidence: 73%
“…These patients are basically managed by government hospitals, which have safe blood transfusion facilities. The main thalassemia center of Sri Lanka is located in Kurunegala and it is supported and guided by a team of international experts under the supervision of the Ministry of Health [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, two recent studies done in India [ 17 ] and Pakistan [ 18 ] reported very high mean serum ferritin values, 2767 and 4236 µg/l, respectively among patients with thalassaemia. An audit done in 2010 in another centre of Sri Lanka noted that almost 50% of patients with β-thalassaemia major had serum ferritin above 2500 µg/l [ 19 ]. This was much higher than what we report; in our cohort only 20% had serum ferritin above 2500 µg/l.…”
Section: Main Textmentioning
confidence: 99%
“…None of the patients had hypothyroidism, hypoparathyroidism or diabetes mellitus. Conversely a Sri Lankan study done among 61 patients few years back reported 7 patients with cardiac failure, 2 with diabetes mellitus, 1 with hypoparathyroidism [ 19 ]. Hepatic alanine aminotransferase were elevated in 13 (24%) of our patients.…”
Section: Main Textmentioning
confidence: 99%